Influence of Human Resource Accounting Practices on Managerial Decision-Making - Abiola, James O.; Adisa, Rilwan Ayinde (Archives of Business Research, 2020)
The study examined the influence of Human Resource Accounting (HRA) practices on managerial decision-making. Data for the study were gathered via a structured questionnaire on a 5-Points Likert Scale administered on personnel of Accounting, and Audit/Internal Control departments which were considered to be the relevant departments for this study in 16 quoted firms in the Nigerian financial services sector. The questionnaires distributed were returned and analyzed using a simple regression analysis model. The study found that HRA has a significant impact on managerial decision-making of organizations. It was therefore recommended that organizations should be more proactive in the use of HRA to enhance decision-making. Necessary and relevant standards should also be provided on the need for recognizing human resource cost in organizations’ statement of financial position in order to enhance adequate decision-making in business organizations premised on fair financial reporting.